HPV DNA frequency and subset analysis in human breast cancer patients' normal and tumoral tissue samples - (:unkn) unknown (APSIT ASSOC PROM STUD IMMUNOL TUMOR, 2006)
Viruses are known to be associated with human malignancies, e.g., Epstein-Barr virus, human papillomavirus (HPV) and human T-cell leukemia virus type I. We conducted a prospective study to define the role of HPV in breast cancer. The malignant and normal breast tissue samples of 50 consecutive breast cancer patients were obtained postoperatively. DNA extracted from all tissues was amplified with the polymerase chain reaction using HPV primers. HPV 11, 16, 18, 33 subtypes were searched in HPV-DNA positive samples. Thirty-seven samples (74%) of tumoral breast tissue expressed HPV-DNA, 16 normal breast tissue samples (32%) were positive as well. There was a significant difference in HPV-DNA positivity between normal and tumoral breast tissue samples. HPV 18 was detected in 20 of the HPV-DNA positive tumoral tissue (54.4%) and in 9 of the HPV-DNA positive normal tissue (56.3%). HPV-33 also was detected in 35 (94.6%) of the HPV-DNA positive tumoral tissue and in 14 (87.5%) of the HPV-DNA positive normal tissue samples. HPV DNA was significantly associated with breast tumor tissue compared to normal breast tissue. Additional studies looking at HPV and HPV subtypes are needed to clarify the etiological role of the HPV in breast cancer.
Keywords: breast cancer; carcinogenesis; human papillomavirus; polymerase chain reaction; prognostic factor; HUMAN-PAPILLOMAVIRUS DNA; CERVICAL-CANCER; WOMEN; CARCINOMA; PREVALENCE; INFECTION; ETIOLOGY; CARCINOGENESIS; TRANSMISSION; SEQUENCES